Prosociality, Political Identity, and Redistribution of Earned Income: Theory and Evidence. - Sanjit Dhami; Emma Manifold; Ali al-Nowaihi (Center for Economic Studies and ifo Institute (CESifo), 2018)
We explore the relation between social political identity and prosociality. We first construct a theoretical model to generate predictions for the behavior of players in an ultimatum game who are influenced by social political identity. Then we use a novel subject pool-registered members of British political parties - to play the ultimatum game, and test our predictions. Incomes can either be unearned and untaxed (Treatment 1) or earned, taxed, and redistributed (Treatment 2). We find that the choices of the proposers and the responders are consistent with social identity theory (higher offers and lower minimum acceptable offers to ingroup members) although proposers show quantitatively stronger social identity effects. Moving from Treatment 1 to Treatment 2, offers by proposers decline and the minimum acceptable offers by responders (both as a proportion of income) also decline by almost the same amount, suggesting shared understanding that is characteristic of social norms.
Keywords: D01; D03; 330; social identity; prosocial behavior; ultimatum game; fiscal redistribution; entitlements